In praise of life. The dynamic concept of biodiversity - Francesc Mesquita-Joanes (Mètode Science Studies Journal: Annual Review)
We humans have long been aware that as a species we have great power to modify the natural world. We sure have. But it has only been a few decades since society, with a firm voice, turned against the destruction carried out in the past. We want to preserve the variety of life forms in all their beauty and complexity, because this biological variety not only provides us physical support, but also promotes our intellectual and philosophical development. It makes us wonder how it emerged, how it works, why species differ from place to place…